Management of exogenous intoxication by carbamates and organophosphates at an emergency unit - Leão,Sydney Correia (2015)
Summary Objectives: to evaluate and indicate the procedure to be followed in the health unit, both for diagnosis and the treatment of acute exogenous intoxications by carbamates or organophosphates. Methods: a descriptive study based on retrospective analysis of the clinical history of patients diagnosed with intoxication by carbamates or organophosphates admitted at the emergency unit of the Hospital de Urgências de Sergipe Governador João Alves (HUSE) between January and December of 2012. Some criteria were evaluated, such as: intoxicating agent; patient's age and gender; place of event, cause, circumstances and severity of the intoxication; as well as signs and symptoms of the muscarinic, nicotinic and neurological effects. Results: seventy patients (average age: 25±19.97) formed the study's population. It was observed that 77.14% of them suffered carbamate intoxication. However, organophosphate intoxications were more severe, with 68.75% of patients presenting moderate to severe forms. Suicide attempt was the leading cause of poisoning, with 62 cases (88.57% of total). Atropine administration was an effective therapeutic approach for treating signs and symptoms, which included sialorrhea (p=0.0006), nausea (p=0. 0029) and emesis (p lt0.0001). The use of activated charcoal was shown effective, both in combating the signs and symptoms presented by both patient groups (p <0.0001). Conclusion: it is concluded that the use of atropine and activated charcoal is highly effective to treat the signs and symptoms developed by patients presenting acute exogenous intoxication by carbamates or organophosphates.